ระดับพฤติกรรมด้านคุณธรรมจริยธรรมของบุคลากร ในสถานศึกษาขั้นพื้นฐาน สำนักงานเขตพื้นที่การศึกษามหาสารคาม เขต 2 Levels of Personnel’s Ethical Behaviors in Basic Education Institutions Under Maha Sarakham Office of Educational Service Area 2 - Thong-in Techakaew ทองอินทร์ เตชะแก้ว (วารสารมหาวิทยาลัยราชภัฏมหาสารคาม, 2015)
การวิจัยนี้มีวัตถุประสงค์ ประการแรกเพื่อศึกษาระดับพฤติกรรมด้านคุณธรรมจริยธรรมของบุคลากรในสถานศึกษาขั้นพื้นฐาน ในสำนักงานเขตพื้นที่การศึกษามหาสารคาม เขต 2 ประการที่สองเพื่อเปรียบเทียบระหว่างผู้ที่มีสถานภาพทางกายภาพ ระดับการศึกษา ประสบการณ์ในการทำงาน และเพศต่างกันต่อพฤติกรรมด้านคุณธรรมจริยธรรม และประการที่สามเพื่อศึกษาแนวทางการพัฒนาพฤติกรรมด้านคุณธรรมจริยธรรมของบุคลากรในสถานศึกษา กลุ่มตัวอย่าง ได้แก่ ผู้บริหารและครู จำนวน 521 คน เครื่องมือการวิจัยเป็นแบบสอบถามแบบมาตราส่วนประมาณค่า 5 การวิเคราะห์ข้อมูลแสดงเป็นค่าร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ทดสอบสมมติฐานด้วย t-test (Independent sample) ผลการวิจัยพบว่า 1. ครูและผู้บริหารในสถานศึกษาขั้นพื้นฐาน สังกัดสำนักงานเขตพื้นที่การศึกษามหาสารคาม เขต 2 มีระดับพฤติกรรม ด้านคุณธรรมจริยธรรมทั้งโดยรวมและรายด้านอยู่ในระดับมาก 2. ครูและผู้บริหารในสถานศึกษาขั้นพื้นฐาน สังกัดสำนักงานเขตพื้นที่การศึกษามหาสารคาม เขต 2 ที่มีสถานภาพและระดับการศึกษาต่างกันมีระดับพฤติกรรมด้านคุณธรรม จริยธรรม ไม่แตกต่างกัน 3. ข้อเสนอแนะพฤติกรรมด้านการครองตน ควรมีการจัดโครงการฝึกอบรมธรรมะสำหรับบุคลากร การจัดโครงการอบรมการดำรงชีวิตแบบพอเพียงสำหรับครอบครัวบุคลากรในสถานศึกษา และควรมีการศึกษาดูงานร่วมกันของบุคลากร พฤติกรรมด้านการครองคน ควรมีการจัดโครงการฝึกทักษะการมีมนุษยสัมพันธ์ มีการฝึกอบรมทักษะการเป็นผู้นำและการให้ขวัญและกำลังใจแก่เพื่อนร่วมงาน พฤติกรรมด้านการครองงาน ควรจัดอบรม สัมมนาเพื่อเพิ่มทักษะใน การปฏิบัติงานแก่ บุคลากร เพิ่มความรู้ทางด้านเทคโนโลยีที่ทันสมัย และส่งเสริมความก้าวหน้าในการทำงานแก่บุคลากร This research aimed to: firstly, study the levels of personnel’s ethical behaviors in basic education institutions under Maha Sarakham Office of Educational Service Area 2; secondly, to compare the levels of ethical behaviors, taking into account physical status, educational qualification, work experience, and gender; and thirdly, study approaches of personnel’s ethical behavior development in the educational institutions. The sample consisted of 521 administrators and teachers. The research instrument was a 5-level rating scale questionnaire. The statistics used in the analysis of data included percentage, mean and standard deviation. And t-test (independent samples) was employed in hypothesis testing. The findings are as follows: 1. The teachers and the administrators in the basic education institutions under Maha Sarakham Office of Educational Service Area 2 had their ethical behaviors, on the whole and by aspect, in the high level. 2. The teachers and the administrators in the basic education institutions under Maha Sarakham Office of Educational Service Area 2, with different status and educational level, had no difference in ethical behavior level. 3. Regarding suggestions, the following were suggested for the development of self-regulating behavior: ethical training projects for the personnel should be provided; training projects on making a living using sufficiency economy should be organized for the personnel’s family; and study tours for the personnel should be organized. In terms of behaviors dealing with others, the following were suggested: training projects on human relation skills should be organized as well as training projects in leadership and colleague encouragement. In terms of working behaviors, the following were suggested: training and seminars for the personnel should be organized in order to enhance their working skills and their knowledge of modern technology; and, the personnel should be promoted to progress in their career.